The Second Incisional Site Metastasis in a Patient with Cervical Carcinoma: A Case Report - Düzgüner, İpek; Üreyen, Işın; Turan, Taner; Tulunay, Gökhan; Boran, Nurettin (Gynecology Obstetrics & Reproductive Medicine, 2013)
Cervical cancer is the third most commonly diagnosed cancer and the fourth leading cause of cancer deaths in females worldwide. Recurrence of carcinoma of the uterine cervix mainly occurs locally or regionally after treatment. Rarely (0.1-1.3%) metastatic recurrence of squamous cervical carcinoma could be identified in the abdominal wall especially in sites of incision. We present a case with a second incisional site metastasis of cervical cancer after seventy five months following first operation.